Pengaruh Partisipasi Dalam Penganggaran Dan Peran Manajerial Pengelola Keuangan Daerah Terhadap kinerja Pemerintah Daerah (Studi Empiris pada SKPD Kabupaten Rokan Hulu) - Yuanna Try Selvi; Vince Ratnawati; Supriono ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study aimed to examine the effect of participation in budgeting and financial management managerial roles with the object of the entire study area SKPDs Rokan Hulu district, consist of 25 SKPD. The research sample are 100 respondents consisting of 13 heads of department, 30 head of sector, 27 head subsections, and 1 hospital director in Rokan Hulu district. Data collected by distributing questionnaires. From 100 questionnaires sent, there were 74 respondents who returns the queationnaires and only 70 questionnaires that can be processed and analyzed. sampling techniques using simple random sampling. The method of data collection is by distributing questionnaires. Analysis using multiple regression. The results of this study we concluded that participation in budgeting and financial management managerial role area significantly positive effect on the performance of local government. In this study the magnitude of the effect that the R2 of 0.230 or 23% indicated that participation in budgeting and financial management managerial roles affect the performance of the local government area by 23%. The results of this study support previous studies.Keywords: Participation in Budgeting, Managerial Role of Financial Management The Local Government Performance.